PESANTREN DAN PENGEMBANGAN PENDIDIKAN PERDAMAIAN Studi Kasus di Pesantren An-Nidzomiyyah Labuan Pandeglang Banten - Muslihah, Eneng (Analisis: Jurnal Studi Keislaman, 2014)
THE  PESANTREN  (BOARDING  SCHOOL)  AND  THE ISLAMIC EDUCATION FOR PEACE DEVELOPMENT: A Case Study in An-Nidzomiyyah Islamic School at Labuan, Pandeglang,Banten: This study attempts to review the pattern of Islamic peace education and its influence on the de-radicalization  of terrorism. The study was conducted  at the Islamic boarding school of An- Nidzomiyah at Labuan, Pandeglang, Banten. Data were collected through questionnaires distributed  to a number of 70 respondents whom  were selected  and  assigned  randomly.  The  study  finds out: First, the rate of Islamic peace education level reached 85% while  the  rate  of de-radicalization   of  terrorism  reaches  81%, which shows the high category and satisfying. Secondly, there is a positive and significant  effect of de-radicalization  of terrorism program as indicated  by a score of 20.40%. The rest is affected by other factors that are still to be investigated. Third, the higher level of the Islamic peace education achievement,  the higher de- radicalization  of terrorism level will be.